Forum Theater: An Innovative Strategy to Enhance Clinician Communication With Marginalized Trauma Patients. Issue 2 (March 2023) - Schombs, Michele; Khedr, Shahenda; Sullivan, Francesca; Alkattan, Abdulaziz; Brown, Candace; Morgan, Liz; Norful, Allison A.; Sample, Jason; Chen, Chun-Cheng
Abstract : BACKGROUND: Marginalized groups experience a higher frequency of traumatic injury and are more likely to report negative experiences in the health care setting. Trauma center staff are prone to compassion fatigue, which impairs patient and clinician interactions for these groups. Forum theater (a form of interactive theater designed for addressing social issues) is proposed as an innovative method of exploring bias and has never been applied in the trauma setting. OBJECTIVE: This article aims to determine the feasibility of implementing forum theater as an adjunct to enhance clinician understanding of bias and its influence on communication between clinicians and trauma populations. METHODS: This is a descriptive qualitative analysis of adopting forum theater at a Level I trauma center in a New York City borough with a racially and ethnically diverse population. The implementation of a forum theater workshop was described, including our work with a theater company to address bias in the health care setting. Volunteer staff members and theater facilitators participated in an 8-hr workshop leading to a 2-hr multipart performance. Participant experiences were collected in a postsession debrief to understand the utility of forum theater. RESULTS: Debriefing sessions after forum theater performances demonstrated that forum theater is a more engaging and effective method for dialogue surrounding bias than personal past experiences with other educational models. CONCLUSION: Forum theater was feasible as a tool to enhance cultural competency and bias training. Future research will examine the impact it has on levels of staff empathy and its impact on participants' level of comfort communicating with diverse trauma populations.